Jeannette Rankin, Republican Party Radical - Shone, Steve J., (Social Sciences E-Books Online, Collection 2026., 2026)
Jeannette Rankin, the first woman to serve in the U.S. Congress, has understandably been celebrated for improving government diversity. However, she did not fit in comfortably with that body's chauvinistic routine, encountering hostility to her ideas, to her gender, and even to her presence during the two terms that she was able to serve. It is the claim of the present work that she is better understood as a radical: a feminist, a pacifist, an advocate for the rights of the poor, a supporter of Irish nationalism, an American Civil Liberties Union leader, and a keen labor union ally.